Genetic analysis of antibiotic resistance in Streptococcus pyogenes. - Stuart, J G (1978)
The genetics of antibiotic resistance in mutant strains of Streptococcus pyrogenes was studied. Utilizing a type 6 strain (9440) primarily resistant to strepttomycin (Strr), classes of mutant strains were isolated that were resistant to one of the following antibiotics: rifampin (Rifr), erythromycin (Eryr), thiostrepton (Tstr), spiramycin (Sprr), fusidic acid (Fusr), gramicidin (Grcr), ethidium bromide (Ebrr), kanamycin (Kanr), neomycin (Neor), oleandomycin (Oler), gentamicin (Genr), and novobiocin (Novr). Transduction experiments separated antibiotic resistance markers into two distinct groups: transducible markers, including Fusr, Bacr, Ksg+, Spcr, Eryr, Sprr, Rifr, Stlr, and Tstr (Bacr, Ksgr, Spcr, and Stlr refer to resistance to bacitracin, kasugamycin, spectinomycin, and streptolydigan, respectively), and nontransducible markers, including Grcr, Ebrr, Kanr, Neor, Oler, Genr, and Novr. By means of two- and three-point crosses, transducible markers (excluding tst) were located in three separate linkage groups. spr was found to be linked with ery and spc in the order spc-ery-spr, whereas in a separate linkage group the order was determined to be str-fus-bac-ksg. The third linkage group contained the rif and stl markers.